Squamous cell carcinoma of maxillary sinus: a comparison of clinico-radiological staging with pre-operative staging - Sudheer, C. P.; Singh, T. Dinesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The nasal cavity and paranasal sinuses are the site of origin of more complex, histologically diverse group of tumors which include neoplasms derived from mucosal epithelium, seromucinous glands and haematolymphoid cells. This study aimed to assess the incidence and prognosis of maxillary sinus malignancy. Methods: A total 25 (16 males, 09 females) malignancy cases between age group 11-70 years. All the cases were undergone with detailed clinical examination. The TNM staging system was followed to detect and standardize the disease stage. CT scan was used to identify the growth and extent of tumor. Results: Majority cases were between the age group 41-50 years (40%). Epistaxis was the commonest clinical symptom in 72% cases followed by nasal obstruction (68%), oral related symptoms (56%), oedema in cheeks (44%) and auditory disturbances in 16% cases. The TNM Staging system showed that 76% cases had T3 lesions, 16% had T4 lesions and 8% had T2 lesions. Nasal symptoms are commonly associated with malignancies and were belongs to T3 stage and few under T4. Conclusions: Maxillary sinus malignancy is an aggressive tumor normally diagnosed at the advanced stage, with minimal prognosis and reduced survival rate. Surgery in combination with radiotherapy followed by chemotherapy remains the best treatment modality.